Effect of substituents of phenyl of π-linkage in carbazole sensitizers on the photovoltaic performance of the dye-sensitized solar cells. (October 2021) - Liao, Chaoqiang; Wu, Hanlun; Fu, Yajie; Zhu, Hengmin; Tang, Hao; Wang, Lingyun; Cao, Derong
Abstract: Four novel carbazole dyes with various substituents, i.e., dyes CA, CO, CP and CB with substituents of alkyl, oxyalkyl, pillar[5]arene and hydrogen, respectively, are designed and synthesized to investigate the relationship between the substituents on phenyl of π-linkage and performances of dye-sensitized solar cells. With the different degree of deviation from planarity of the π-linkage by the substituents, the HOMO level and bandgap of the dyes were selectively tuned. The dye CO shows lower HOMO (0.66 V) and E0-0 (2.23 eV) than that of CB (HOMO: 0.97 V, E0-0 : 2.52 eV), leading to the enhanced light harvesting ability and thus the highest power conversion efficiency among the four dyes. Further study shows that the bridge of carbon atoms between the substituents and phenyl in the dyes CA and CP decreased the short-circuit photocurrent, lower their performance. This study shows that the substituents can affect the torsion angle of π-linkage, the charge recombination, the electron lifetime for photoexcited electron injection into the TiO2 and V OC, which paves the way to design dyes for highly efficient solar cells. Graphical abstract: Image 1 Highlights: Carbazole dyes are synthesized by changing substituents on phenyl of π-linkage. The additional substituents inhibit charge recombination. The larger torsion angle of π-linkage, the longer electron lifetime. The larger torsion angle of π-linkage, the higher V OC . Oxyalkyl substituents improve the planarity of π-linkage, increasing J SC .